(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the interrelationship between language and culture from the perspective of linguoculturology. The article provides a general overview of linguoculturology, a discipline that emerged at the intersection of linguistics and cultural studies. It discusses its object, subject, methodology, and main analytical unit — the linguocultureme. Additionally, the study demonstrates how elements of national mentality, cultural stereotypes, and worldview are reflected in somatic phraseological units used in English and Uzbek languages.